2018
DOI: 10.1016/j.yebeh.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with refractory temporal lobe epilepsy and mesial temporal sclerosis: Possible association with major depressive disorder?

Abstract: The present study observed significantly higher serum levels of MDA and of TEAC in patients with refractory TLE-MTS in comparison with the control group. The MDD was observed as an important issue associated with higher OS levels in refractory TLE-MTS. Further studies are needed to investigate the association of OS, TLE-MTS, and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Patients with epilepsy have a three-fold risk for psychiatric comorbidities compared to the general population [2]. Almost 20-22% of patients with epilepsy suffer from depression [2][3][4][5][6][7], while its prevalence may reach 60% in patients with temporal lobe epilepsy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with epilepsy have a three-fold risk for psychiatric comorbidities compared to the general population [2]. Almost 20-22% of patients with epilepsy suffer from depression [2][3][4][5][6][7], while its prevalence may reach 60% in patients with temporal lobe epilepsy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in this series MDA levels showed high sensibility and specificity, indicating discriminatory power and a potential prognostic tool for oxidative stress in patients with schizophrenia, according to another study (Pawar and Abhang, 2017). In contrast, similar values of TEAC, which correspond to the antioxidant capacity and protection against free radicals and reactive oxygen species (Gilca et al, 2014;Filho et al, 2018), were showed in all groups, but reduced level in patients using antipsychotics was also reported (Gilca et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Oxidative stress, an imbalance between reactive oxygen species and antioxidant agents, can be measured also by biomarkers such as malondialdehyde (MDA), a byproduct of lipid peroxidation that impairs the functioning of neuronal cells (Emiliani et al, 2014;Liencres et al, 2014;Pawar and Abhang, 2017;Zheng et al, 2019). Additionally, the competence of antioxidant components can be evaluated by the trolox equivalent antioxidant capacity (TEAC) (Gilca et al, 2014;Filho et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a significant association between suicidal behaviors and oxidative toxicity including elevated AOPP levels was reported [76]. Moreover, de Araujo Filho et al [31] observed that MDA levels were significantly increased in comorbid TLE patients and depression. Nevertheless, in our study, mood disorders due to TLE with depressive symptoms and anxiety disorders due to TLE are accompanied by somewhat lowered MDA levels, while anxiety disorders due to TLE also show a lower lowered oxidative stress toxicity index than patients with TLE without these comorbidities.…”
Section: Discussionmentioning
confidence: 92%
“…The association between redox status and psychosis is more complex, with no or minimal changes being observed in first-episode psychosis [28,29] and in chronic schizophrenia [30], although deficit, but not non-deficit schizophrenia, is accompanied by increased levels of AOPP and lipid hydroperoxides (LOOH), but not MDA, and lowered levels of -SH groups and TRAP (Maes et al, in preparation). A recent study showed that MDA levels were significantly higher in TLE patients with depression than in those without [31], suggesting that this comorbidity may increase oxidative stress toxicity.…”
Section: Introductionmentioning
confidence: 99%